Differences in the effect of health promotion media using booklets and audio visuals on the level of caries knowledge 6th grade student dental 09 Aie Pacah Elementary School - M. Dzulkarnain Al-Madani; Darmawangsa Darmawangsa; Sri Pandu Utami (Politeknik Kesehatan Kemenkes Aceh, 2022)
Dental and oral health problems generally occur due to low public knowledge about good oral and dental care. This study aimed to determine the effect of health promotion media using booklets and audiovisuals on the level of dental caries knowledge of 6th-grade students of SDN 09 Aie Pacah. This type of research is quantitative, using a quasi-experimental method with a two-group pretest-posttest research design. The research sample comprised 58 respondents who were divided into 2 groups, namely 29 respondents for each group, using the total sampling technique. Data analysis includes paired t-tests and independent t-tests. The results showed the difference in knowledge before and after dental caries health education in respondents with booklet media (p= 0,000) and audiovisual media (p= 0,000). There was no difference between the groups who had been given health education using booklets and audiovisual media on the dental caries knowledge of 6th graders at SDN 09 Aie Pacah (p= 0,863). In conclusion, booklets and audiovisual media increase knowledge about dental caries health in elementary school children. There is no difference in dental health education using the booklet and audiovisual media.